KAJIAN PENERAPAN PP NO. 46 TAHUN 2013 TENTANG PPh ATAS PENGHASILAN DARI USAHA WAJIB PAJAK YANG MEMILIKI PEREDARAN BRUTO TERTENTU DI KOTA SEMARANG - Saifudin .; Fariz Nur H (STIE Pelita Nusantara Semarang, 2016)
This study aims to determine the application of PP 46 Year 2013 concerning income tax on income from business taxpayers who have a certain gross turnover. The population in this study is the company's clients in tax consulting firm Core Development Management (IPM) Semarang. The sample in this study were taken by purposive sampling method. Data were analyzed using descriptive studies. The test results of this study with a sample of 12 companies is Tax Article 25 and PP 46 applied to the taxpayer of the various types of enterprise entity that has gross income below 4.8 M in the first year, which is listed as a client in tax consulting firm Core Development Management (IPM) Semarang No 9 Corporate Taxpayers who benefit from the tariff Tax Article 25 and 3 Corporate Taxpayers who benefit from the tariff Regulation No. 46 Year 2013.